Stabilized Porous Phospholipid Nanoshells - Cheng, Zhiliang (2006)
Chemically stabilized, porous phospholipid nanoshells (PPNs) were prepared via copolymerization of reactive monomers with unilamellar bis-Sorbyl phosphatidylcholine vesicles. The resulting PPN vesicular assemblies possess a highly porous membrane structure that allows passage of small molecules, which can react with encapsulated proteins and reporters. The unique combination of membrane stability and porosity will prove useful for preparing nm-sized sensor, container and reactor platforms stable in harsh chemical and biological environments.